Comparative characteristics of the efficiency of different methods of determining meat coils with numbers on the surface of the Aberdeen-Angus breed - Колісник, О. І.; Прудніков, В. Г.; Криворучко, Ю. І.; Нагорний, С. А. (Scientific Progress & Innovations, 2018)
Breeding cattle is the most important means of making beef production in the conditions of meat cattle breeding, which saves a significant amount of concentrated feed, labor resources, fuel and lubricants, and gives the opportunity to get high-quality cheap beef. In conditions of the Eastern region of Ukraine, when raising the beef of the Aberdeen-Angus breed, resource-saving technology of meat cattle breeding is used. The purpose of these studies was to carry out a comparative study of the various methods of grazing beef cattle with calves in the subsystem on natural pastures and to establish the most effective, low-cost method with subsequent calculations of technological maps with consistent operational processes taking into account labor costs per day and the entire pasturing period. It was found that labor costs significantly influenced the way of grazing livestock, especially when using electric paddle, horse, or foot. Thus, the rates of time spent using the electric heath make up 0,54 minutes/head during its installation and 1,28 minutes/head for general operations, using a horse and grazing on foot – 8,75 and 11,5 min/head, respectively. The greatest percentage of man-hours expenses is attributable to general operations: when grazing on foot is 85.3 %, while grazing with a horse – 81.4 %, and with the use of electric paddle – 45.3 %, including the installation of electrical appliances – 10 %. That is, the advantage of economical use of human labor was on the side of the last method of grazing cattle. Total labor costs in other organically-technological operations of the pasturing period, such as loading, transportation, distribution of feed for the feeding of calves and cows, as well as the supply of water, were 1080 human-hours/per period. In order to ensure the fulfillment of all the necessary technological processes and operations in keeping the Aberdeen-Angus cows with calves on the subspecies (220 heads) during the grazing period, natural grazing in the conditions of the Forest-Steppe of Ukraine requires the following number of workers: when grazing on foot – 9 people, while grazing with a horse – 7.5 people, using electric paddle – 4 people. Consequently, the expediency of wider use of electric paddles in grazing livestock has been established due to the saving of human labor, fewer workers and more efficient use of pastures.